Impelementasi Pelaksanaan Pembelajaran Kurikulum 2013 dengan Pendekatan Saintifik Tema III Peduli Terhadap Makhluk Hidup - Tusyana, Eka; Markhumah, Ulum Fatimatul (Al-Riwayah : Jurnal Kependidikan, 2021)
The purpose of this study is to describe the implementation of the curriculum 2013 learning implementation with a scientific approach to theme III caring for living things in class IV SD Negeri 1 Kauman Jombang. The learning aspect activities include the initial learning activities, the core learning activities, and the closing learning activities. This type of research is qualitative with a phenomenological approach. Data collection techniques in this study are observation, interviews, and documentation. The results of this study indicate that the implementation of the curriculum 2013 learning with a scientific approach to theme III cares about living things 1) The initial activities are carried out in accordance with the Appendix contained in Permendikbud of the Republic of Indonesia Number 103 of 2014 which is humorous, caring, assertive, making children relax in learning, arouse students' enthusiasm. 2) The core activities are carried out by meeting the standards of implementing scientific learning approaches such as making observations, asking questions, gathering information / asking questions, and associating. 3) Closing activities are carried out properly in accordance with the closing activities of the learning process which includes closing learning activities, conducting assessments, concluding learning materials, providing feedback on the learning process and learning outcomes, as well as conveying learning material to be learned at the next meeting